2018
DOI: 10.1097/sla.0000000000002614
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Dual-ring Wound Protector for Prevention of Surgical Site Infections After Pancreaticoduodenectomy in Patients With Intrabiliary Stents

Abstract: Among adult patients with intrabiliary stents, the use of a dual-ring wound protector during PD significantly reduces the risk of incisional SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
1
35
1
1
Order By: Relevance
“…None of the patients in this series had an incision protector in place during surgery. There is evidence that such devices may benefit patients in terms of reducing SSI rates [15]. Although this recent trial looked only at patients with biliary stents, the SSI rate in the cohort in which a wound protector was used was 27.3%, which is similar to the rate in the current study in which cefazolin was used.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…None of the patients in this series had an incision protector in place during surgery. There is evidence that such devices may benefit patients in terms of reducing SSI rates [15]. Although this recent trial looked only at patients with biliary stents, the SSI rate in the cohort in which a wound protector was used was 27.3%, which is similar to the rate in the current study in which cefazolin was used.…”
Section: Discussionsupporting
confidence: 69%
“…Although this recent trial looked only at patients with biliary stents, the SSI rate in the cohort in which a wound protector was used was 27.3%, which is similar to the rate in the current study in which cefazolin was used. In the study by Bressan et al [15] study, the use of antibiotic prophylaxis was not standardized or controlled for on the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis did not identify any significant modifying factor relationships (estimated blood loss, duration of surgery, hospital site, etc.) (P > 0.05) [63].…”
Section: Resultsmentioning
confidence: 83%
“…A similar effect size was found in the subgroup of patients undergoing colorectal surgery (risk ratio 0.65; 95%CI, 0.44-0.97; P = 0.04; I 2 2 = 56%). Of the two common types of wound Table 3 The effectiveness of wound protectors [57][58][59][60][61][62][63]: characteristics of the studies included in the review. RCT: randomized controlled trial; SSI: surgical site infection; PCT: prospective controlled trial; GoR: grade of recommendation protectors, double-ring devices were found to exhibit a greater protective effect (risk ratio 0.29; 95%CI, 0.15-0.55) than single-ring devices (risk ratio 0.71; 95%CI, 0.54-0.92), but this might largely be due to the lower quality of available data for double-ring devices.…”
Section: Resultsmentioning
confidence: 99%
“…A wound bundle, in general, will have more than three components and extend from pre-operative care through to rehabilitation. Fundamental to a bundle is timely antibiotic administration, glucose control, prevention of hypothermia, hypotension and hyperglycaemia combined with newer concepts including incisional negative pressure therapy [12] and wound protective devices [13,14].…”
Section: Introductionmentioning
confidence: 99%